Gambaran Aktivitas Fisik Lansia di Panti Tresna Werdha Kecamatan Ciparay Kabupaten Bandung - Anggi Saputra; Mery Thania; tita puspita ningrum; Nurul Iklima; Cica Iklima (LPPM Universitas Adhirajasa Reswara Sanjaya, 2025)
The elderly are individuals who are at the end of the stage of human life, where the process of decline is more dominant than progress. Poor sleep quality can be influenced by several factors such as age, motivation, physical activity, diet, culture, alcohol consumption, smoking, lifestyle, and disease. Regular physical activity in the elderly such as cleaning the house, doing physical exercise and others can stimulate a decrease in sympathetic nerve activity and an increase in parasympathetic activity which results in a decrease in the hormones adrenaline, norepinephrine and catecholamines so as to help fulfill the quality of sleep in the elderly. The purpose of this study was to analyze the relationship between physical activity and sleep quality in the elderly. This research method uses a cross sectional study research design. The population of this study were all elderly people who were in the Tresna Werda Panti, Ciparay District, Bandung Regency. The number of samples in this study were 50 respondents with a sampling technique using purposive sampling. The instrument used in this study used the PASE questionnaire to measure physical activity and the PSQI questionnaire to measure sleep quality. Analysis of the data using the formula for the frequency distribution and Spearman rank. The results of this study were obtained from 50 respondents 47 (94.0%) elderly had less physical activity, 48 (96.0%) elderly had poor sleep quality. Therefore, it is very important to have structured physical activity programs/activities for the elderly at the Tresna Werda Panti, Ciparay District, Bandung Regency.